Kedudukan Istri Siri Sebagai Ahli Waris dalam Perspektif Hukum Waris Islam di Indonesia - Nanda Eka Prasetya; Mira Diva Prasyanti; Miskha Ainun Nisa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research discusses the position of a siri wife as an heir based on a will from the perspective of Islamic inheritance law. According to the context of Islamic law, the position of an unregistered wife is often a problem, especially in relation to the inheritance rights that she should receive. This research aims to examine how wills can affect the inheritance rights of siri wives. The method used is literature study with analysis using data collection techniques through literature study or document study, which is the most appropriate method for normative legal research. The research results show that even though the siri wife is not recognized as a legal wife in the context of positive law, the will made by the husband can give the siri wife inheritance rights. However, this recognition depends on the intention and clarity in the preparation of the will. It is hoped that this research can provide a better understanding of the rights of unregistered wives in the Islamic inheritance system and encourage the need for reform in inheritance law regulations in Indonesia to create justice for all parties.